2020
DOI: 10.1007/s40121-020-00303-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatments Administered to the First 9152 Reported Cases of COVID-19: A Systematic Review

Abstract: The emergence of SARS-CoV-2/2019 novel coronavirus (COVID-19) has created a global pan-demic with no approved treatments or vaccines. Many treatments have already been administered to COVID-19 patients but have not been systematically evaluated. We performed a systematic literature review to identify all treatments reported to be administered to COVID-19 patients and to assess time to clinically meaningful response for treatments with sufficient data. We searched PubMed, BioRxiv, MedRxiv, and ChinaXiv for arti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 45 publications
2
60
0
2
Order By: Relevance
“…[64][65][66] Almost 60 years of experience in the prophylaxis and therapy of a variety of clinical conditions have established the safety of this drug, even at very high doses and for long-term treatments. Drug repurposing is the fastest strategy toward an effective and accessible treatment against COVID-19 before a vaccine is available, 67 and molecules working via multiple mechanisms of action, such as NAC, are more likely to be effective as compared with drugs having a single target.…”
Section: Resultsmentioning
confidence: 99%
“…[64][65][66] Almost 60 years of experience in the prophylaxis and therapy of a variety of clinical conditions have established the safety of this drug, even at very high doses and for long-term treatments. Drug repurposing is the fastest strategy toward an effective and accessible treatment against COVID-19 before a vaccine is available, 67 and molecules working via multiple mechanisms of action, such as NAC, are more likely to be effective as compared with drugs having a single target.…”
Section: Resultsmentioning
confidence: 99%
“…The first study performed a systematic review of published studies that reported drug therapies for COVID-19 patients. 3 The authors screened 2706 publications and identified 155 published studies that met their inclusion criteria. Two individuals read all 155 studies and manually extracted information about administered drugs into spreadsheets, and a third person reviewed the extracted data to resolve discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is beneficial to disseminate this information quickly, culling information from this large publication volume can be difficult and time-consuming. 3 There is a tremendous amount of information relating to symptoms at the onset of disease, and disease symptoms, treatments, and management for hospitalized patients. Responses of individual patients can vary widely, from asymptomatic or mild disease to multi-organ failure and death.…”
Section: Introductionmentioning
confidence: 99%
“…However, information on trials that are planned, ongoing, finished, or published are spread across trial registries, preprint servers, publication databases and other repositories. In June, 2020, the number of ongoing trials outweighed by far completed trials; however, no overview of COVID-19 trials has followed up on actual enrolment in ongoing trials [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%